EMOTIONAL RELATIONSHIP BETWEEN TEACHERS AND STUDENTS IN ELEMENTARY SCHOOL NEGERI 3 BANDA ACEH CITY - Rita Yusari; Siti Mayang Sari; Sariakin; Fitriani Manurung; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Teachers are unsung heroes in educating and imparting knowledge to their students responsibly andsincerely. Teachers also guide and always provide motivation to their students. The teacher is thesecond parent who is responsible for the learners while in school. Teachers should be role models andexamples inside and outside the school. Based on facts seen in SD Neg 3 Banda Aceh, teachersalways make themselves parents for their students. This study aims to investigate teacher strategies inbuilding emotional connections between teachers and students in Sd Neg 3 Banda Aceh City. In thisstudy using qualitative methods by conducting class observations, interviews and documentation. Theresults showed that by the way teachers recognize and help their students effectively can help teachersin building positive relationships with their students. From the findings described above, it can beconcluded that the formation of an emotional connection between teachers and students at SD Neg 3Banda Aceh City has a very positive impact so that it makes didk participants and teachers in theteaching and learning process can be well established and the results of these students get satisfactoryfinal results.